(untitled) (Journal of Comparative & International Higher Education, 2022)
Norway has large unrealized potential for recruiting students from Africa. In order to increase student mobilisation and integration, it is important to know the potential challenges students from underrepresented continents are likely to face in an environment with severe sociocultural differences. This study examined experiences of 7 international students from East Africa studying in a larger city in Norway. Data was collected through semi-structured in-depth interviews, and grounded theory was applied. Analyses of the data resulted in the development of a process model, illustrating three main phases international students went through. The initial phase shows the financial, social, and emotional challenges that students faced. In the transitional phase they found social support from students in similar situations, whereas in the settling phase they tended to mobilize individual and social resources for coping. The results are discussed in light of previous research and concluded with recommendations for higher education institutions.